The Legal Effects Of Deed Creation Of Probate Inheritance That Does Not Match With The Principle Of Absolute Section (A Case Study of Decision No. 539 / Pdt.G / 2012 / PN.Jkt.Bar Jo. Decision No. 477 / Pdt.G / 2014 / PT.DKI) - Pangeran Roeslan Amiril Moekminin; Abdul Haris (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
This study aims to identify and analyze: 1) The legal consequences Deeds Wills made by or before a Notary, if contrary to the principle of absolute section; 2) How inheritance dispute settlement in accordance with the Civil Code; 3) Law of Evidence applied by judges in the dispute settlement deed Testament heritage as opposed to the absolute part Heirs according to the Civil Code in the Register of Case No. 539 / Pdt.G / 2012 / PN.Jkt.Bar Jo. Decision No. 477 / Pdt.G / 2014 / PT.DKI.Based on the results of this research is that: 1) the Deed of wills that exceeds Legitime portie the Heirs of Ab intestato not immediately lead to the deed will be null and void or not legally binding, but still valid, as long as not canceled by the court decision; 2) Settlement of disputes of inheritance for the citizen who are not followers of Islam based on the provisions of inheritance as specified by the Civil Code; 3) At the Appellate Judges stated that the Deed of Wills number 15 made by Tjeng To Ho in front of Notary Mrs. Nani Susanti, SH is a legitimate and valuable, but for the sake of protecting the inheritance Heirs The Ab intestato, so the Judge court based on article 914 paragraph 3 stated that the heirs Ab intestato which include 7 persons each other have the part ¾ section, while the heirs Ad testamento got ¼ part left.Keywords: Miraculous Deeds; Legitime Portie; Legal Effects.